Study on the method of enucleation of anterior uterine fibroids by transverse incision of the lower uterine segment during cesarean section - Yan Dai; Li Xia; Jinxiao Lin; Rongli Xu; Wenqiang You (BMC, 2021)
Abstract Introduction A retrospective study was conducted to investigate the effectiveness and feasibility of fibroid enucleation in the anterior wall of the uterus by transverse uterine incision during cesarean section. Methods The medical history, surgical data, preoperative and postoperative changes in the blood system, and complications of 90 pregnant women who underwent myomectomy of the anterior uterine wall during cesarean section at the second Department of Maternal and Child Health Hospital of Fujian Province were analyzed retrospectively. Results No significant differences were noted in the leiomyoma number, pathological type, preoperative and postoperative hemoglobin level, perioperative bleeding incidence, blood transfusion frequency, postoperative fever incidence, and duration of lochia between the study and control groups. The proportion of large fibroids was slightly higher in the study group than in the control group (p < 0.05), and the operation time and average hospitalization time were slightly longer in the study group than in the control group (p < 0.05). The distribution of type III-V fibroids was slightly more in the study group than in the control group (p < 0.05), and the distribution of type VI fibroids in the study group was less than that in the control group (p < 0.05). Conclusion Fibroid enucleation is safe and effective in the anterior wall of the uterus through the lower uterine transverse incision in cesarean section. It has the potential to reduce the risk of pelvic and intrauterine adhesions in the future.